2004
DOI: 10.1111/j.1461-0248.2004.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Allee effects, mating systems and the extinction risk in populations with two sexes

Abstract: The Allee effect is one of the population consequences of sexual reproduction that has received increased attention in recent years. Due to its impact on small population dynamics, it is commonly accepted that Allee effects should render populations more extinction prone. In particular, monogamous species are considered more susceptible to the Allee effect and hence, more extinction prone, than polygamous species. Although this hypothesis has received theoretical support, there is little empirical evidence. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
172
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(179 citation statements)
references
References 31 publications
5
172
0
2
Order By: Relevance
“…Longer-term monitoring of another set of experimental populations (18) showed similar amplification of sex ratio bias (40% initially, 61% after 4 years, n ϭ 16), parallel with a sustained population decline and high extinction rates (18). Thus, the deleterious demographic effects of male excess on females raise a major threat to population persistence that had not been previously recognized (2,13,14). To quantify this extinction risk and to analyze its sensitivity to male and female behavior, we constructed a stage-structured stochastic population model.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…Longer-term monitoring of another set of experimental populations (18) showed similar amplification of sex ratio bias (40% initially, 61% after 4 years, n ϭ 16), parallel with a sustained population decline and high extinction rates (18). Thus, the deleterious demographic effects of male excess on females raise a major threat to population persistence that had not been previously recognized (2,13,14). To quantify this extinction risk and to analyze its sensitivity to male and female behavior, we constructed a stage-structured stochastic population model.…”
Section: Resultsmentioning
confidence: 68%
“…In fact, males and females often differ in their vital rates, density dependence, and sensitivity to the environment (9). Nonmanipulative studies have identified possible consequences of sex structure on population dynamics (9,11), including reproductive collapse after male rarity (13). By experimental manipulation, long-term monitoring, and mathematical projections of populations of common lizards, we demonstrate rigorously that male-biased ASRs exacerbate male aggression and become deleterious to females, which amplifies further the sex ratio biases toward males and leads to a positive feedback of population decline, that is, an extinction vortex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, intense selective harvesting of populations can cause annual variations in ASR (Ginsberg and Milner-Gulland, 1994;Bender and Miller, 1999;Milner-Gulland et al, 2003;Milner et al, 2007). Understanding what factors cause annual variation in the ASR of a population will assist biologists in conserving populations that possess high levels of demographic stochasticity or manage important game species that are subject to an intense annual harvest (Wildt and Wemmer, 1999;Wedekind, 2002;Bessa-Gomes et al, 2004).…”
Section: Introductionmentioning
confidence: 99%